Mutations in the MAB_2299c TetR Regulator Confer Cross-Resistance to Clofazimine and Bedaquiline in Mycobacterium abscessus - Richard, Matthias (Antimicrob Agents Chemother, 2018)
New therapeutic approaches are needed against Mycobacterium abscessus, a respiratory mycobacterial pathogen that evades efforts to successfully treat infected patients. Clofazimine and bedaquiline, two drugs used for the treatment of multidrug-resistant tuberculosis, are being considered as alternatives for the treatment of lung diseases caused by M. abscessus. With the aim to understand the mechanism of action of these agents in M. abscessus, we sought herein to determine the means by which M. abscessus can develop resistance. Spontaneous resistant strains selected on clofazimine, followed by whole-genome sequencing, identified mutations in MAB_2299c, encoding a putative TetR transcriptional regulator. Unexpectedly, mutants with these mutations were also cross-resistant to bedaquiline. MAB_2299c was found to bind to its target DNA, located upstream of the divergently oriented MAB_2300-MAB_2301 gene cluster, encoding MmpS/MmpL membrane proteins. Point mutations or deletion of MAB_2299c was associated with the concomitant upregulation of the mmpS and mmpL transcripts and accounted for this cross-resistance. Strikingly, deletion of MAB_2300 and MAB_2301 in the MAB_2299c mutant strain restored susceptibility to bedaquiline and clofazimine. Overall, these results expand our knowledge with respect to the regulatory mechanisms of the MmpL family of proteins and a novel mechanism of drug resistance in this difficult-to-treat respiratory mycobacterial pathogen. Therefore, MAB_2299c may represent an important marker of resistance to be considered in the treatment of M. abscessus diseases with clofazimine and bedaquiline in clinical settings.